The Impact of Metformin on the Development of Hypothyroidism and Cardiotoxicity Induced by Cyclophosphamide, Methotrexate, and Fluorouracil in Rats - Ahmad H. Alhowail; Maha A. Aldubayan (MDPI AG, 2023)
Cyclophosphamide (CYP), methotrexate (MTX), and 5-fluorouracil (5-FU) are extensively utilized in the therapeutic management of various malignancies. It is noteworthy, however, that potential chemotherapy-related complications include the occurrence of hypothyroidism and cardiotoxicity. Metformin (MET) is a pharmacological agent for managing type 2 diabetes. It has been reported to mitigate certain toxic manifestations associated with chemotherapy. This study's primary objective is to investigate MET's protective effects against hypothyroidism and cardiotoxicity induced by CMF treatment. A total of forty male rats were allocated into four distinct groups, each consisting of ten rats per group. These groups were categorized as follows: saline, MET, CMF, and CMF + MET. The experimental group of rats were administered CMF via intraperitoneal injection, receiving two doses of CMF, and fed MET in their daily drinking water, with a 2.5 mg/mL concentration. Blood samples were collected into EDTA tubes for assessment of TSH, free and total (T4 and T3), troponin I, CK, and CK-MB levels utilizing Electrochemiluminescence Immunoassays (ECI). The saline and MET groups did not exhibit significant alterations in thyroid hormones or cardiotoxic biomarkers. In contrast, in the CMF group, there was a notable reduction in T4, FT4, T3, and FT3 levels but no significant changes in TSH levels; however, troponin I, CK, and CK-MB levels were notably elevated. MET co-treatment with CMF did not ameliorate these effects caused by CMF. In conclusion, CMF treatment induced hypothyroidism and cardiotoxicity in rats, but MET co-treatment did not rescue the reduction of thyroid hormones or the elevation of cardiotoxic biomarkers.